The Dynamics Of Illegitimate Child Status In Sharia And National Law Of Indonesia: Is There A Harmonization? - Habibi, Ahmad Rizza (Al-Manhaj: Journal of Indonesian Islamic Family Law, 2021)
Putusan Mahkamah Konstitusi Nomor 46/PUU-VIII/2010 adalah upaya reformasi hukum. karena menilai anak di luar nikah memiliki status yang sama dengan anak lainnya. meski terdapat ketidakharmonisan antara keputusan dan pengaturan bagi anak yang lahir di luar nikah akibat zina dalam hukum Islam. Artikel ini mengungkap peran Majelis Ulama Indonesia (MUI) terhadap proses harmonisasi hukum. Putusan ini menerapkan konsep Sadd al-Dzari'ah untuk menutupi kemungkinan zina sekecil apa pun sekaligus melindungi hak-hak anak. (The decision of the Constitutional Court Number 46/PUU-VIII/2010 is an effort to reform the law because they judge that children out of wedlock have the same status as other children. However, disharmony exists between decisions and arrangements for children born out of wedlock due to adultery in Islamic law. This article reveals the Indonesian Ulama Council (MUI) legal harmonization process. However, this decision applies the concept of Sadd al-Dzari'ah to cover the slightest possibility of adultery while protecting children's rights.)